(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Construction of a house is a life time dream for every individual. Before taking decision about to housing loan everyone will go through different perceptions. The present study reveals their comparisons of about availing funds as a source of their housing finance. They will see all banks operations which are providing housing finance and also observe all types of state and central government schemes, and there after they will compare one with other schemes and also banks. The present study focusing on comparison between public and private banks in Visakhapatnam district of A.P how they providing loans to their customers along with making them beneficial.